Inductive detection of fieldlike and dampinglike ac inverse spin-orbit torques in ferromagnet/normal-metal bilayers - Berger, Andrew J.; Edwards, Eric R. J.; Nembach, Hans T.; Karenowska, Alexy D.; Weiler, Mathias; Silva, Thomas J. (Physical Review B, 2018)
Functional spintronic devices rely on spin-charge interconversion effects, such as the reciprocal processes of electric field-driven spin torque and magnetization dynamics-driven spin and charge flow. Both dampinglike and fieldlike spin-orbit torques have been observed in the forward process of current-driven spin torque and dampinglike inverse spin-orbit torque has been well studied via spin pumping into heavy metal layers. Here, we demonstrate that established microwave transmission spectroscopy of ferromagnet/normal metal bilayers under ferromagnetic resonance can be used to inductively detect the ac charge currents driven by the inverse spin-charge conversion processes. This technique relies on vector network analyzer ferromagnetic resonance (VNA-FMR) measurements. We show that in addition to the commonly extracted spectroscopic information, VNA-FMR measurements can be used to quantify the magnitude and phase of all ac charge currents in the sample, including those due to spin pumping and spin-charge conversion. Our findings reveal that Ni80Fe20/Pt bilayers exhibit both dampinglike and fieldlike inverse spin-orbit torques. While the magnitudes of both the dampinglike and fieldlike inverse spin-orbit torque are of comparable scale to prior reported values for similar material systems, we observed a significant dependence of the dampinglike magnitude on the order of deposition. This suggests interface quality plays an important role in the overall strength of the dampinglike spin-to-charge conversion.
CRIS-Team Scopus Importer:2023-03-27